A comparative study of two devices used for cervical cell sampling raises some doubts about liquid-based cytology. Issue 4 (1st July 2006) - Kothari, A.; Karim, S. Z.; Gordon, A.; Raslan, F.; Abdalla, M.; George, S.
Abstract : The objective of this study was to compare the quality of smears obtained by a newly designed cervical cell sampler (the implement) to those obtained with the cervex brush, using liquid-based cytology (LBC). A prospective randomized controlled trial with the approval of the local ethics committees after informing the Medical Devices Agency in the UK was used in this study. The study was carried out in colposcopy clinics in two district general NHS Trust Hospitals in London. A total of 200 women were recruited (100 from each hospital). The women were randomized into two groups, each of them having two smears at the same time. One hundred (50%) of the women had their first smear with the new implement, and the other 100 (50%) had their first smear with the cervex brush. The main outcome of this study is good-quality smears, assessed by evidence of effective sampling of the transformation zone, including immature metaplastic cells and also endocervical cells. Eighty-five percent of the smears taken by the new implement showed good-quality smears compared to 91% of those taken by the cervex brush, a statistically marginally nonsignificant result, with P value = 0.052 (McNemar exact test). A larger number of good-quality smears, judged by evidence of sampling of transformation zone, were obtained with the cervex brush, though the difference was statistically marginally nonsignificant, using the British society for clinical cytology criteria. Surprisingly, despite the use of LBC, there was a higher rate of inadequate smears obtained with both the devices (8% with each) compared to our previous study using the conventional slide test (1.3% with the new implement and 1.8% with the Jordan's spatula).